The Impact of Metformin on Reducing Inflammation, Edema, and Colonic Tissue Damage in Rats with Acetic Acid–Induced Ulcerative Colitis - Seyyed Navid Mousavinejad; Samira Heydari; Amin Derakhshanfar; Razieh Sabet Sarvestani; Mohammad Ali Takhshid (Journal of Mazandaran University of Medical Sciences)
Background and purpose: Oxidative stress and inflammation play a significant role in the development of ulcerative colitis. Consequently, antioxidant and anti-inflammatory agents may be effective in treating this condition. Metformin is recognized as both an anti-inflammatory and antioxidant agent. This study aimed to investigate the effects of metformin on alleviating inflammation and tissue damage in a rat model of experimentally induced ulcerative colitis. Materials and methods: Twenty-four Wistar rats were randomly divided into four groups (n = 6 each): control, non-treated colitis, metformin-treated colitis (125 mg/kg), and metformin-treated colitis (250 mg/kg). Metformin treatment was initiated two days prior to and continued for three days following the induction of colitis. Colitis was induced by intrarectal administration of 3% acetic acid. Three days after colitis induction, the animals were sacrificed, and macroscopic and microscopic assessments of colonic tissue damage were performed. These included evaluations of inflammation, leukocyte infiltration, crypt necrosis, and edema. Results: Macroscopic colonic damage, including the number and extent of ulcers and tissue edema, was significantly higher in the colitis group compared to the control group (P< 0.001). Metformin administration significantly reduced macroscopic lesions compared to the colitis group (P< 0.001). At the microscopic level, colitis caused crypt necrosis, severe leukocyte infiltration of the colonic wall, and increased thickness of the smooth muscle layer compared to the control group (P< 0.001). In both metformin-treated groups, microscopic damage was significantly lower than in the colitis group (P< 0.001). Conclusion: These results suggest that metformin can ameliorate ulcerative colitis in an experimental model and may be considered a promising therapeutic option for its treatment.